The melanocytic proliferations : a comprehensive textbook of pigmented lesions - Crowson, A. Neil; Magro, Cynthia M.; Mihm, Martin C. (Wiley-Blackwell, 2014)
A thorough updating of the best-selling, vital reference and textbook on melanocytic proliferations PRAISE FOR THE FIRST EDITION: "Well-written and entertaining" — Modern Pathology "An extremely helpful guide for the practicing dermatopathologist or general pathologist" — Archives of Pathology and Laboratory Medicine "An incredibly relevant clinical-histopathologic text" — Doody's Melanocytic proliferations comprise a large number of pigmented lesions of the skin and muscosa. Of these, melanoma is of particular interest to clinicians and their patients. The rising number of incidences of melanoma has led to increased interest in the disease from diagnostic, management, and basic science perspectives. The Melanocytic Proliferations: A Comprehensive Textbook of Pigmented Lesions is the most complete single-source treatment of the subject available—thoroughly updated to reflect the very latest studies and clinical experience in diagnosing and treating melanocytic proliferation. This new edition of the bestseller presents an experience- and evidence-based review of pigmented lesions that encompasses the biology, diagnosis, and treatment of melanocytic proliferations and disorders, including melanoma. It comes with over 300 new color images—bringing the total to over 600—and contains two completely new chapters: Dermatoscopic Diagnosis of Melanoma; and Reflectance Confocal Microscopy. Chapter coverage includes: • An approach to the clinical diagnosis of melanoma, its precursors, and its clinical mimics • Freckles and lentigines • Benign acquired nevi • Dermal dendritic melanocytic proliferations/dermal melanocytoses • Spitz nevus • Combined nevus, deep penetrating nevus, plexiform spindle cell nevus, and borderline tumors of the deep penetrating nevus variant • Recurrent melanocytic nevus • Congenital nevi • Dysplastic melanocytic nevi, de novo intradermal epithelioid and lentiginous melanocytic dysplasias, and nevi at specific anatomic sites • Melanoma • Conjunctival melanocytic proliferations • Use of adjunctive immunoperoxidase, molecular, and ultrastructural studies in the diagnosis of melanocytic proliferations • Biology of melanoma • Borderline melanocytic proliferation • Dermatoscopic diagnosis of melanoma • Reflectance confocal microscopy • Therapy of melanoma The Melanocytic Proliferations: A Comprehensive Textbook of Pigmented Lesions is an incredibly important text for all clinical pathologists, dermatopathologists, surgical pathologists, dermatologists, cosmetic physicians, and surgeons.